Fleece and Felt as Substrates for Patch Antenna at 2.4GHz - Azahari, Badrul Amin; Kamardin, Kamilia; Fitri Othman, Muhammad Syamim; Mad Kaidi, Hazilah (International Journal of Integrated Engineering, 2025)
This study examines the integration of textile patch antennas with high-gain antennas in apparel, highlighting applications in wearable electronics. One potential application is in patient apparel, where the antenna enables the wireless transmission of cardiac monitoring data. The study investigates key aspects of textile patch antennas, utilizing textile fleece and textile felt as the base substrates. This includes simulation of design parameters, a production method employing copper conductive paint as the metallic material, and measurement protocols for the fabricated antennas. Measurements were conducted using a Vector Network Analyzer (VNA) to determine impedance matching, and within an anechoic chamber to analyze radiation patterns and gain. The outcomes from the design and measurement processes showed a strong correlation, with the exception of the felt-based antenna’s gain, which may have been affected by either a fault in the antenna or an error during measurement.